Development of a database on key characteristics of human carcinogens. (17th November 2019) - Al-Zoughool, Mustafa; Bird, Michael; Rice, Jerry; Baan, Robert A.; Billard, Mélissa; Birkett, Nicholas; Krewski, Daniel; Zielinski, Jan M
ABSTRACT: A database on mechanistic characteristics of human carcinogenic agents was developed by collecting mechanistic information on agents identified as human carcinogens (Group 1) by the International Agency for Research on Cancer (IARC) in the IARC Monographs on the Evaluation of Carcinogenic Risks to Humans . A two-phase process is described for the construction of the database according to 24 toxicological endpoints, derived from appropriate test systems that were acquired from data obtained from the mechanisms sections of the IARC Monographs (Section 4) and a supplementary PubMed search. These endpoints were then aligned with 10 key characteristics of human carcinogens that reflect the broader attributes of these agents relating to the development of cancer in humans. The considerations involved in linking of toxicological endpoints to key characteristics are described and specific examples of the determination of key characteristics for six specific agents (tamoxifen, hepatitis B virus, arsenic, ultraviolet and solar radiation, tobacco smoking, and dioxin) are provided. Data for humans and animals were tabulated separately, as were results for in-vivo and for in-vitro sources of information. The database was constructed to support a separate analysis of the expression of these endpoints by 86 Group 1 carcinogens, in-vivo and in-vitro along with an analysis of the key characteristics of these agents.